Mechanical properties of plain woven kenaf/glass fiber reinforced polypropylene hybrid composites - Dhar Malingam, Sivakumar; Subramaniam, Kathiravan; Ng, Lin Feng; Sheikh Md Fadzullah, Siti Hajar; Subramonian, Sivarao (Carl Hanser Verlag, München, 2019)
There has been an increasing interest among researchers on natural/ synthetic hybrid fiber reinforced composites due to their extensive advantages such as enhanced mechanical properties as compared to natural fiber reinforced composites. The balance between environmental friendliness and mechanical strength can be achieved through hybrid composite materials. This study aims to investigate the effects of stacking sequences on the mechanical properties of woven kenaf/glass hybrid composites. Woven kenaf/glass hybrid composites with two different stacking sequences were fabricated in the hot compression process. Non-hybrid glass and kenaf fiber reinforced polypropylene composites were also prepared for comparison. Tensile, flexural and Charpy impact tests were conducted in accordance with ASTM D 3039, ASTM D 790 and ASTM D 6110, respectively. The results showed that the tensile strength of glass/kenaf/glass hybrid laminates was only 3.4 % lower than that of non-hybrid glass fiber reinforced composites. The flexural strength of hybrid glass/kenaf/glass laminates was 32.5 % higher than non-hybrid glass fiber reinforced composites. In terms of impact strength in edgewise and flatwise orientations, hybrid glass/kenaf/glass laminates showed 8.6 % and 51.9 % improvement, respectively, as compared to non-hybrid glass fiber reinforced composites. This showed that the hybrid laminates exhibited superior mechanical properties as compared to non-hybrid glass fiber reinforced composites.